A comparative assessment of anaerobic digestion power plants as alternative to lagoons for vinasse treatment: life cycle assessment and exergy analysis. (1st February 2016) - Barrera, Ernesto L.; Rosa, Elena; Spanjers, Henri; Romero, Osvaldo; De Meester, Steven; Dewulf, Jo
Abstract: The treatment of vinasse in lagoons causes methane emissions during the anaerobic decomposition of the organic matter. The recovery of this methane, to produce renewable energy in anaerobic digestion power plants (ADPPs) replacing fossil fuels and reducing greenhouse gas emission, could bring environmental benefits. The aims of this work were: (1) to compare alternatives of ADPPs available for the treatment of vinasse; and (2) to evaluate the impacts of ADPPs as alternative for lagooning Cuban vinasse; both by means of Life Cycle Assessment (LCA) and exergy analysis (EA). The LCA and EA showed that the ADPPs improve the environmental profile with respect to the lagooning of vinasse, reducing up to 77% the total score and recovering up to 46% of the exergy extracted from the natural environment during the process, respectively. The highest environmental benefits for the ADPPs were observed when the subprocesses biogas production from raw vinasse, sulfide removal by biooxidation with air oxygen addition and energy generation in spark ignition engines were used. In that case, the treatment of 1072 ton of vinasse (exergy content of 740.6 GJex ) can produce 175 GJex as "electricity and heat", 191 GJex as "wastewater for fertirrigation", 21.7 GJex as "digestate", and 0.41 GJex as "sulfur in the filter cake". This way, the produced 1.3 million cubic meters of vinasse (1.34·10 6 ton/year) reported by the Cuban Ministry of the Cane Sugar Industry can replace 485263 GJex per year as energy and bio-fertilizers, reducing the negative environmental impacts for the studied categories. Highlights: Impacts of anaerobic digestion power plants v. lagooning were assessed for vinasse. The best options of anaerobic digestion power plants were proposed for vinasse. Based on LCA, anaerobic digestion power plants can reduce the total impact by 77%. Exergy efficiencies up to 46% can be obtained in anaerobic digestion power plants. 24% of the exergy content of vinasse can be converted into useful energy.